Chronic Pathology and Longevity of Drepanocephalus spathans Infections in Juvenile Channel Catfish. Issue 4 (17th September 2014) - Griffin, Matt J.; Khoo, Lester H.; Steadman, James M.; Ware, Cynthia; Quiniou, Sylvie M.; Mischke, Charles C.; Greenway, Terrence E.; Wise, David J.
Abstract: Drepanocephalus spathans (Digenea: Echinostomatidae) is a common parasite of the double‐crested cormorant Phalacrocorax auritus . The cercariae of D. spathans have been shown infective to juvenile Channel Catfish Ictalurus punctatus . The developing metacercariae concentrate in the cranial regions, often occluding blood vessels at the base of the branchial arch, occasionally resulting in death. The purpose of this study was to determine how long metacercariae of D. spathans persist in experimentally challenged Channel Catfish. Two separate infectivity trials were conducted. In both trials, metacercariae persisted at least 49 d postinfection, although prevalence and intensity of infection decreased over time. In the first trial, juvenile catfish (1–3 g) were exposed over three consecutive days to 100, 100, and 80 cercariae/fish/d, respectively. Fish were sampled 7 d after the final exposure, and metacercariae were observed in 83.3% (five of six) of challenged fish. At 21 d postexposure, metacercariae were present in only 50% of exposed fish (three of six). No metacercaria were observed in fish sampled at 35 d, however, metacercariae were present in one of six (16.7%) fish sampled 49 and 70 d postexposure, respectively. A second challenge consisted of a 24‐h pooled exposure of 500 cercariae per fish. Again, metacercariae were present in most (six of seven; 85.7%) fish at 7 d postexposure. At 21 d postexposure, metacercariae were only evident in one of seven (14.3%) sampled fish. No metacercariae were present in any fish at 35 d postchallenge, yet one of seven (14.3%) fish was positive at 49 d postchallenge. The second study was terminated at 63 d postchallenge, as all fish sampled ( n = 14) were negative for metacercariae. These data suggest that cercariae of D. spathans are infective to juvenile Channel Catfish, although the infection appears short lived as metacercariae rarely persisted longer than 2 months. Received February 14, 2014; accepted May 30, 2014